PARENTING STYLES AND CLASSROOM SOCIAL INTERACTION AMONG SENIOR HIGH SCHOOL STUDENTS - Norman Mark A. Ramento (Galaxy International Interdisciplinary Research Journal, 2021)
The purpose of quantitative correlational study was to determine the relationship between demographic profile, the parenting styles, and classroom social interaction of the respondents. This study included 209 senior high school students of Quinapondan National High School. The respondents accomplished the questionnaire pertaining to assess parenting style and classroom social interaction of the respondents. Quantitative data analysis methods were used including mean, frequency count and percentage as well as correlational analysis. Age has no significant relationship with the parenting styles. It reflects an index of correlation at .137 and p-value .270. Sex also shows no correlation with the parenting styles. It has an index of correlation .068 and p-value .033. Grade level shows no significant relationship with the parenting styles. There is an index of correlation of .027 and p-value of .694. Strand shows no significant relationship with the parenting style. There is an index of correlation of .137 and p-value of .141. Family income has a low correlation with the parenting style but has no significance with the index of correlation of .223 and p-value of .141. Lastly, educational attainment of parents has also a low correlation and has significance with the parenting styles in the index of correlation of .241 and p-value of .016. Parenting styles has a significant relationship with the classroom social interaction of the student. There is an index of correlation of .377 and p-value of .000. This study suggested that students must encourage themselves to actively participate in class. They must show their full potential to be productive in every activity given to them by the teachers. Teachers must have a close monitoring of the students and must immediately give feedback and share it with parents so that hand in hand, both teachers and parents can make interventions on how to enhance students’ classroom participation. Parents must undergo seminars on good parenting. Since they are the source of strength and motivation of the students to perform well in class.